A hydrophobic wire mesh for better liquid dispersion in air. (12th October 2017) - Zhang, Jing-Peng; Luo, Yong; Chu, Guang-Wen; Sang, Le; Liu, Yi; Zhang, Liang-Liang; Chen, Jian-Feng
Graphical abstract: The structure-performance relationship of the hydrophobic surface-modified RPB packing enhances the macro-dispersion of liquid. Highlights: A hydrophobic surface-modified stainless steel wire mesh was prepared. Liquid splashing was studied by using a high-speed camera. The cone angle generated by the SSM was larger than that of the NSM. A correlation was established to predict the mean droplet diameter. Rosin–Rammler distribution appropriately represents the droplet size distribution. Abstract: Liquid dispersion significantly affects the mass transfer performance in chemical systems, such as in a rotating packed bed (RPB). Previous studies focused on the structure and type of packing to improve the liquid dispersion for better mass transfer performance. However, using a packing with a hydrophobic surface for liquid dispersion enhancement has scarcely been assessed. Our research prepared a hydrophobic surface-modified stainless steel wire mesh (SSM), already widely used as packing. SEM and XPS analyses demonstrate that the hydrophobicity of the SSM is due to the co-effect of the low-energy coating material used and its rough surface with microstructures. The SSM has shown high stability and adhesivity. Liquid dispersion was studied by using a high-speed camera when liquid passes through the SSM layer. Investigation covered the effects of surface hydrophobicity, liquid velocity, liquid surface tension and viscosity on the cone angle, mean droplet diameter, and droplet size distribution, by analyzing the photographs recorded by the camera. The cone angle generated by the SSM was larger than that of a non-surface-modified stainless steel wire mesh (NSM) under the same experimental conditions. The mean droplet diameter obtained by the SSM was smaller than that of the NSM. A correlation was established to predict the mean droplet diameter, and the predicted values were found to be in agreement with the experimental values with deviations generally within ±10%. The Rosin–Rammler distribution (RRD) can appropriately represent the droplet size distribution.